# |
ODE |
Mathematica |
Maple |
\[
{}y^{\prime \prime \prime \prime }+2 y^{\prime \prime \prime }-2 y^{\prime \prime }+8 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\left (5\right )}+4 y^{\prime \prime \prime \prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\left (5\right )}+4 y^{\prime \prime \prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\left (5\right )}+3 y^{\prime \prime \prime \prime }+3 y^{\prime \prime \prime }+y^{\prime \prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }+2 y^{\prime \prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }+8 y^{\prime \prime }+16 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\left (6\right )}+3 y^{\prime \prime \prime \prime }+3 y^{\prime \prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\left (6\right )}+12 y^{\prime \prime \prime \prime }+48 y^{\prime \prime }+64 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-2 y^{\prime \prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }+16 y^{\prime \prime \prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }-8 y^{\prime \prime }+16 y = 0
\] |
✓ |
✓ |
|
\[
{}24 y^{\prime \prime \prime }-26 y^{\prime \prime }+9 y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }-5 y^{\prime \prime }+4 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }-16 y = 0
\] |
✓ |
✓ |
|
\[
{}8 y^{\left (5\right )}+4 y^{\prime \prime \prime \prime }+66 y^{\prime \prime \prime }-41 y^{\prime \prime }-37 y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 y^{\left (5\right )}+7 y^{\prime \prime \prime \prime }+17 y^{\prime \prime \prime }+17 y^{\prime \prime }+5 y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\left (5\right )}+8 y^{\prime \prime \prime \prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\left (6\right )}-3 y^{\prime \prime \prime \prime }+3 y^{\prime \prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+9 y^{\prime \prime }+16 y^{\prime }-26 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }+12 y^{\prime \prime \prime }+60 y^{\prime \prime }+124 y^{\prime }+75 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+3 y^{\prime \prime }+2 y^{\prime }+6 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }-8 y^{\prime \prime \prime }+30 y^{\prime \prime }-56 y^{\prime }+49 y = 0
\] |
✓ |
✓ |
|
\[
{}\frac {31 y^{\prime \prime \prime }}{100}+\frac {56 y^{\prime \prime }}{5}-\frac {49 y^{\prime }}{5}+\frac {53 y}{10} = 0
\] |
✓ |
✓ |
|
\[
{}x^{3} y^{\prime \prime \prime }+22 x^{2} y^{\prime \prime }+124 x y^{\prime }+140 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{3} y^{\prime \prime \prime }-4 x^{2} y^{\prime \prime }-46 x y^{\prime }+100 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{3} y^{\prime \prime \prime }+2 x^{2} y^{\prime \prime }-4 x y^{\prime }+4 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{3} y^{\prime \prime \prime }+4 x^{2} y^{\prime \prime }+6 x y^{\prime }+4 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{3} y^{\prime \prime \prime }+2 x y^{\prime }-2 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{3} y^{\prime \prime \prime }+3 x^{2} y^{\prime \prime }-2 x y^{\prime }-2 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{3} y^{\prime \prime \prime }+6 x^{2} y^{\prime \prime }+7 x y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}x^{3} y^{\prime \prime \prime \prime }+6 x^{2} y^{\prime \prime \prime }+7 x y^{\prime \prime }+y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x^{3} y^{\prime \prime \prime }+10 x^{2} y^{\prime \prime }-20 x y^{\prime }+20 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{3} y^{\prime \prime \prime }+15 x^{2} y^{\prime \prime }+54 x y^{\prime }+42 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{3} y^{\prime \prime \prime }-2 x^{2} y^{\prime \prime }+5 x y^{\prime }-5 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{3} y^{\prime \prime \prime }-6 x^{2} y^{\prime \prime }+17 x y^{\prime }-17 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{3} y^{\prime \prime \prime }+3 x^{2} y^{\prime \prime }+37 x y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x^{3} y^{\prime \prime \prime }+3 x^{2} y^{\prime \prime }-3 x y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x^{3} y^{\prime \prime \prime }+x y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}x^{3} y^{\prime \prime \prime }+16 x^{2} y^{\prime \prime }+79 x y^{\prime }+125 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{4} y^{\prime \prime \prime \prime }+5 x^{3} y^{\prime \prime \prime }-12 x^{2} y^{\prime \prime }-12 x y^{\prime }+48 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{4} y^{\prime \prime \prime \prime }+14 x^{3} y^{\prime \prime \prime }+55 x^{2} y^{\prime \prime }+65 x y^{\prime }+15 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{4} y^{\prime \prime \prime \prime }+8 x^{3} y^{\prime \prime \prime }+27 x^{2} y^{\prime \prime }+35 x y^{\prime }+45 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{4} y^{\prime \prime \prime \prime }+10 x^{3} y^{\prime \prime \prime }+27 x^{2} y^{\prime \prime }+21 x y^{\prime }+4 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{3} y^{\prime \prime \prime }+9 x^{2} y^{\prime \prime }+44 x y^{\prime }+58 y = 0
\] |
✓ |
✓ |
|
\[
{}2 y^{\prime \prime \prime }+3 y^{\prime \prime }+y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}9 y^{\prime \prime \prime }+36 y^{\prime \prime }+40 y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}9 y^{\prime \prime \prime }+12 y^{\prime \prime }+13 y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime } = \sqrt {1-{y^{\prime \prime }}^{2}}
\] |
✓ |
✗ |
|
\[
{}x y^{\prime \prime \prime }-y^{\prime \prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+{y^{\prime \prime }}^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime } = 3 y y^{\prime }
\] |
✗ |
✓ |
|
\[
{}y^{\prime \prime \prime }-3 y^{\prime \prime }+3 y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+6 y^{\prime \prime }+11 y^{\prime }+6 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\left (6\right )}+2 y^{\left (5\right )}+y^{\prime \prime \prime \prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-8 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }+4 y^{\prime \prime \prime }+10 y^{\prime \prime }+12 y^{\prime }+5 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }+2 y^{\prime \prime \prime }+4 y^{\prime \prime }-2 y^{\prime }-5 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\left (5\right )}+4 y^{\prime \prime \prime \prime }+5 y^{\prime \prime \prime }-6 y^{\prime }-4 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+2 y^{\prime \prime }-y^{\prime }-2 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-2 y^{\prime \prime }+2 y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\left (5\right )} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-3 y^{\prime }-2 y = 0
\] |
✓ |
✓ |
|
\[
{}2 y^{\prime \prime \prime }-3 y^{\prime \prime }+y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+y^{\prime \prime } = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime \prime }-3 x y^{\prime \prime }+3 y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime \prime } = 2 y^{\prime }
\] |
✓ |
✓ |
|
\[
{}\left (1+x \right )^{2} y^{\prime \prime \prime }-12 y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\left (2 x +1\right )^{2} y^{\prime \prime \prime }+2 \left (2 x +1\right ) y^{\prime \prime }+y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+y^{\prime \prime }-y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }-\lambda ^{4} y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime \prime \prime }+4 x y^{\prime \prime \prime }+2 y^{\prime \prime } = 0
\] |
✓ |
✓ |
|
\[
{}x^{3} y^{\prime \prime \prime \prime }+6 x^{2} y^{\prime \prime \prime }+6 x y^{\prime \prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+y^{\prime \prime }+y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }-4 y^{\prime \prime \prime }+6 y^{\prime \prime }-4 y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }-9 y = 0
\] |
✓ |
✓ |
|
\[
{}t \left (t -1\right ) y^{\prime \prime \prime \prime }+{\mathrm e}^{t} y^{\prime \prime }+4 t^{2} y = 0
\] |
✗ |
✗ |
|
\[
{}\left (x -4\right ) y^{\prime \prime \prime \prime }+\left (1+x \right ) y^{\prime \prime }+\tan \left (x \right ) y = 0
\] |
✗ |
✗ |
|
\[
{}\left (x^{2}-2\right ) y^{\left (6\right )}+x^{2} y^{\prime \prime }+3 y = 0
\] |
✗ |
✗ |
|
\[
{}y^{\prime \prime \prime \prime }+5 y^{\prime \prime \prime }+4 y = 0
\] |
✓ |
✓ |
|
\[
{}t \left (t -1\right ) y^{\prime \prime \prime \prime }+{\mathrm e}^{t} y^{\prime \prime }+7 t^{2} y = 0
\] |
✗ |
✗ |
|
\[
{}\left (x -1\right ) y^{\prime \prime \prime \prime }+\left (x +5\right ) y^{\prime \prime }+\tan \left (x \right ) y = 0
\] |
✗ |
✗ |
|
\[
{}\left (x^{2}-25\right ) y^{\left (6\right )}+x^{2} y^{\prime \prime }+5 y = 0
\] |
✗ |
✗ |
|
\[
{}y^{\prime \prime \prime }+y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }+y^{\prime \prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+4 y^{\prime \prime }-4 y^{\prime }-16 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }+6 y^{\prime \prime \prime }+9 y^{\prime \prime } = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime \prime \prime }-y^{\prime \prime } = 0
\] |
✓ |
✓ |
|
\[
{}x^{3} y^{\prime \prime \prime }+x^{2} y^{\prime \prime }-2 x y^{\prime }+2 y = 0
\] |
✓ |
✓ |
|
\[
{}a^{3} y^{\prime \prime \prime } y^{\prime \prime } = \sqrt {1+c^{2} {y^{\prime \prime }}^{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime } = \sqrt {1+{y^{\prime \prime }}^{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-x y^{\prime \prime \prime }+{y^{\prime \prime \prime }}^{3} = 0
\] |
✓ |
✓ |
|
\[
{}5 {y^{\prime \prime \prime }}^{2}-3 y^{\prime \prime } y^{\prime \prime \prime \prime } = 0
\] |
✓ |
✓ |
|
\[
{}40 {y^{\prime \prime \prime }}^{3}-45 y^{\prime \prime } y^{\prime \prime \prime } y^{\prime \prime \prime \prime }+9 {y^{\prime \prime }}^{2} y^{\left (5\right )} = 0
\] |
✓ |
✓ |
|
\[
{}2 x^{3} y^{\prime \prime \prime }-6 x^{2} y^{\prime \prime }+12 x y^{\prime }-12 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-\frac {3 y^{\prime \prime }}{x}+\frac {6 y^{\prime }}{x^{2}}-\frac {6 y}{x^{3}} = 0
\] |
✓ |
✓ |
|
\[
{}x^{3} y^{\prime \prime \prime }-3 x^{2} y^{\prime \prime }+6 x y^{\prime }-6 y = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime \prime \prime }-y^{\prime \prime }+x y^{\prime }-y = 0
\] |
✓ |
✓ |
|